"I am not the person I used to be": Perceptions and experiences of menopausal women living in Karachi, Pakistan. Issue 4 (December 2021) - Asad, Nargis; Somani, Rozina; Peerwani, Nausheen; Pirani, Shahina; Zuberi, Nadeem; Andrades, Marie; Karmaliani, Rozina
Objective: The study aims to explore the perceptions and experiences of menopausal women living in Karachi, Pakistan. Study design: Using qualitative exploratory design, in-depth interviews were conducted with eleven women, aged 35–55 years. The data was collected through face-to-face interviews using semi structured interview guide. Creswell frame work for content analysis was used to analyze the data. Main outcome measures: Perceptions and experiences of menopause women living in Karachi, Pakistan. Results: Women described positive and negative experiences of menopause, though predominantly negative intensified by mental distress, lack of support from intimate partner, and misperceptions about menopause. A majority of the women emphasized the need for educating their husbands regarding menopausal changes. In clinical practices, health care professionals should screen the women for menopause challenges when they visit health care facilities and offer education regarding self-care and management to achieve better quality of life and positive coping. Conclusions: We conducted a preliminary study on women's perceptions and experiences of menopause in the context of Pakistan. Our study offers significant findings from an Asian cultural perspective, in which norms are predominantly patriarchal and male dominated. The study provides useful guidelines for health care providers to better address health care needs of menopausal women.